Rapid Separation of All Four Tocopherol Homologues in Selected Fruit Seeds via Supercritical Fluid Chromatography Using a Solid-Core C18 Column - Elise Urvaka; Inga Mišina; Arianne Soliven; Paweł Górnaś (Journal of Chemistry)
Tocopherol separations employing the same Kinetex™ C18 column via supercritical fluid chromatography (SFC) and reversed-phase liquid chromatography (RP-LC) were compared. The application of the SFC system with UV diode array detection (DAD) resulted in rapid separation of all four tocopherol homologues with a total analysis time below 2 min. The RP-LC approach could not separate the isomers β and γ. The developed SFC-DAD method was precise, accurate, and most importantly more environmentally friendlier compared to the RP-LC method due to the 125-fold decrease in methanol consumption. The present study illustrated the selectivity differences between LC and SFC and how the C18 column can be used for tocopherol characterization. The optimized SFC method was successfully applied for the tocopherol determination in the seeds of nine different fruit species.